2013
DOI: 10.1111/adj.12022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of beta‐2 microglobulin and alpha‐2 macroglobulin levels in patients with different periodontal diseases

Abstract: Background: Beta-2 microglobulin (B2M) and alpha-2 macroglobulin (A2M) play key roles in the immune system. The aim of this study was to compare B2M and A2M levels in patients with different periodontal diseases. Methods: Eighty patients (20 periodontally healthy, 20 with gingivitis, 20 with chronic periodontitis and 20 with generalized aggressive periodontitis) were enrolled in the study. The analysis of B2M and A2M was performed on gingival crevicular fluid (GCF) using an enzyme-linked immunosorbent assay in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
0
16
0
1
Order By: Relevance
“…While potential pleiotropic effects of A2ML1 remain to be fully resolved, our data showed that A2ML1 variants are not associated with oral disease. Previously A2M protein was found to be higher in gingival crevicular fluid of patients with gingivitis and chronic periodontitis, but whether A2M plays a role in pathogenesis or is merely a marker for inflammation is unknown (Ertugrul, Sahin, Dikilitas, Alpaslan, & Bozoglan, ). We first hypothesized that the structural similarity between A2M and A2ML1 might translate to an increased risk for dental disease conferred by A2ML1 variants.…”
Section: Discussionmentioning
confidence: 99%
“…While potential pleiotropic effects of A2ML1 remain to be fully resolved, our data showed that A2ML1 variants are not associated with oral disease. Previously A2M protein was found to be higher in gingival crevicular fluid of patients with gingivitis and chronic periodontitis, but whether A2M plays a role in pathogenesis or is merely a marker for inflammation is unknown (Ertugrul, Sahin, Dikilitas, Alpaslan, & Bozoglan, ). We first hypothesized that the structural similarity between A2M and A2ML1 might translate to an increased risk for dental disease conferred by A2ML1 variants.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen papers were reviewed. Case definitions and methodologic approaches differed substantially . Of note, Teles et.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Case definitions and methodologic approaches differed substantially. 27,[75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91] Of note, Teles et. al.…”
Section: Generalized Aggressive Periodontitismentioning
confidence: 99%
“…A2M is a protease inhibitor known to exert a key role in the immune system although its mechanisms are not completely understood. It is associated with tissue destruction in periodontitis and is suggested to inhibit inflammation and to suppress proliferation of microorganisms[63]. A2M is also implicated in cartilage degradation, it is known to interact with the osteogenic growth peptide, osteoprotegerin (OPG), and suggested to inhibit BMP-1[64].…”
Section: Discussionmentioning
confidence: 99%